Development of SIBENI Interactive Learning Media Using Unity for Indonesian Cultural Arts - Lana, Muhammad Isfa'; Widodo, Suprih (UNDIKMA, 2026)
This research aims to develop SIBENI educational applications as an interactive learning media for Nusantara arts and culture that can increase the interest and understanding of elementary school students. The development was carried out using the Multimedia Development Life Cycle (MDLC) method through the stages of concept, design, material collection, assembly, testing, and distribution, accompanied by functionality tests using black box testing, usability tests with the System Usability Scale (SUS), and content validity using the Learning Object Review Instrument (LORI) instrument by material experts. The test results show that the SIBENI application functions optimally with a 100% suitability level, obtaining a SUS score of 88.5 (category A+ / Best Imaginable), and 100% content validity, which indicates the application is easy to use, stable, and presents accurate and appropriate materials. These findings have an impact on increasing the effectiveness of arts and culture learning, while contributing to the preservation of Nusantara culture through the provision of digital media that is attractive, easily accessible, and relevant to modern learning needs.